Enhancing high-temperature strength of (B4C+Al2O3)/Al designed for neutron absorbing materials by constructing lamellar structure. (15th February 2020) - Zan, Y.N.; Zhou, Y.T.; Zhao, H.; Liu, Z.Y.; Wang, Q.Z.; Wang, D.; Wang, W.G.; Xiao, B.L.; Ma, Z.Y.
Abstract: Aiming at developing new generation of high-temperature neutron absorbing materials for both structural and functional usages, (B4 C + Al2 O3 )/Al composites were fabricated. Hot forging and extruding were carried out to adjust the microstructures of the composites. The forged samples exhibited a lamellar structure with Al2 O3 staying at the grain boundaries. In the extruded sample, most Al2 O3 entered into the interior of ultrafine-grains. Different strengthening effects of intergranular and intragranular Al2 O3 at room and high temperatures were studied. It was verified that Al2 O3 distributed at the grain boundaries was more beneficial to enhance the high-temperature strength by strengthening the grain boundaries and preventing dislocations from annihilating, therefore the forged samples were much stronger than the extruded sample at 375 °C. The sample forged with a height reduction ratio of 8:1 showed an ultimate strength of 342 MPa at room temperature and an ultimate strength of 96 MPa at 375 °C.